Molecular Docking of The Potential Compound from Cocoa Shells (Theobroma cacao L.) Against Androgen Receptor as Anti-Alopecia - Resmi Mustarichie (Journal of Global Pharma Technology, 2020)
The determination of the components of the cocoa shells compounds that have anti-alopecia activity have not been reported, so the molecular docking approach is a very effective alternative before further testing is carried out. This study aimed to determine the potential compound components against androgen receptor targets as anti-alopecia drugs. Molecular docking used ChemDraw Ultra 12.0, Chem3D Pro 12.0, Biovia Discovery Studio 2016 Client®, and Autodock Tools 4.2, as well as to determine the pharmacokinetic properties and toxicity of drug ingredients with Pre-ADMET. It was found that that the components of the cocoa peel compound had the potential to act as anti-alopecia drugs, namely chlorogenic acid, epicatechin, and catechins with the value of the free energy binding (ΔG) and the inhibition constant (Ki) respectively (-7.87 kcal/mol; 1.70 µM)> (-6.48 kcal/mol; 17.65 µM)> (-6.36 kcal/mol; 21.91 µM) with the crucial amino acid residue formed was GLN 858. The pharmacokinetics (plasma protein binding) of epicatechin and catechin were excellent compared to chlorogenic acid and minoxidil because it could penetrate the plasma membrane when interacting. While the toxicity test, the components of chlorogenic acid, epicatechin, and catechin compounds were mutagenic, and only chlorogenic acid was carcinogenic. The study concluded chlorogenic acid, epicatechin, and catechin compounds from the cocoa shells were promising candidates for anti-alopecia drugs to be developed further targeting androgen receptors. It was consistent with the molecular docking results, which showed that ΔG and Ki's values were excellent compared to minoxidil. The pre-ADMET results also showed that the epicatechin and catechin compounds components could penetrate the plasma membrane when given topically compared to minoxidil. Keywords: Alopecia, Cocoa shells, Theobroma cacao, Molecular docking, Androgen receptor.